(untitled) (Scientific journal of the Fergana State University, 2024)
This article provides evidence to support the hypothesis that digital tools enhance student engagement and participation in the classroom. The findings highlight the benefits of integrating digital tools in education, including increased student engagement, active participation and personalized learning experiences. Nowadays, language teachers should know how confidently integrate a variety of digital tools into their lesson plans and maintain an effective learning environment there language class. It is of a great importance to get necessary knowledge to integrate these apps into the classroom as valuable tools to support each student learning style.